PENYELENGGARAAN PENDIDIKAN INKLUSIF BAGI ANAK TUNANETRA LOW VISION (Deskriptif Kualitatif di SMAN 3 Padang) - Riri Rahayu (Universitas Negeri Padang, 2014)
ABSTRAK This research was conducted based on the importance of conducting inclusive education well. In its implementation, it should consider about the learning principles which were adjusted to the students’ characteristics. In addition, the accessibility of the students with special needs should be taken into account. This research was designed for revealing the implementation of inclusive education and accessibility of the students with low vision. This research was conducted at SMAN 3 Padang Kata kunci: Aksesibilitas; Low Vision; Pelaksanaan pembelajaran; Pendidikan Inklusif; Tunanetra;